Repair of horizontal root fracture: A case report - Shafie, Laila; Farzaneh, Farhad; Hashemipour, Maryam Alsadat (Iranian Endodontic Journal, 2011)
ABSTRACT: Horizontal root fractures in permanent teeth are uncommon injuries among dental traumas. The principle of treating horizontal root fractures of permanent teeth is repositioning and fixation of fractured segment. Diagnosis of tooth fractures based on radiographic findings and the fracture healing process are affected by factors before and after injury. The present case reports the treatment of horizontal root fracture located at the apical-third of upper left and right central incisors. Healing was observed at 1 year follow-up examination.